Lance Nematode, Hoplolaimus galeatus (Cobb, 1913) Thorne, 1935 (Nematoda: Secernentea: Tylenchida: Tylenchoidea: Hoplolaimidae) - William T. Crow; Angela S. Brammer (EDIS)
Among nematodes, which are often too small to be accurately detected by sight, the lance nematode Hoplolaimus galeatus (Cobb, 1913) Thorne, 1935, is one of the larger species. As adults they measure about 1.5 mm in length. Although other species of lance nematodes can be very damaging to agronomic crops, H. galeatus is known primarily as a pest of turfgrasses. This document is EENY-234, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001.